17β-Estradiol promotes the synthesis and the secretion of annexin I in the CCRF-CEM human cell line. Issue 5 (2001) - Castro-Caldas Castro-Caldas, Margarida Margarida; Duarte Duarte, Carlos B. Carlos B.; Carvalho Carvalho, Arsélio P. Arsélio P.; Lopes Lopes, M. Celeste M. Celeste
Abstract : Aims: Annexin I (ANXA1), a 37 kDa member of the annexin family of Ca 2+ -binding and phospholipidbinding proteins, is particularly abundant in various populations of peripheral blood leukocytes. Since this protein modulates the anti-inflammatory actions of the steroid hormones, the purpose of this study was to investigate the effects of the female sex steroid hormone, 17β-estradiol (E2 β), on the synthesis and secretion of ANXA1 in the human CCRF-CEM acute lymphoblastic leukemia cell line. Methods: Complementary reverse transcription-polymerase chain reaction and Western blot assays were performed to study the effect of E2 β on the expression of mRNA and protein ANXA1, respectively. Results and discussion: Treatment of CCRF-CEM cells with E2 β, for 30 min, stimulated the synthesis of ANXA1 mRNA molecules, and increased the cellular level of ANXA1 protein. Moreover, when the cells were incubated with E2 β, under the same experimental conditions, a significant increase in the amount of ANXA1 secreted from the cells was also detected. ICI 182, 780, a selective inhibitor of the intracellular estrogen receptor, had no effect on the E2 β-stimulated expression and externalisation of ANXA1. Taken together, these results indicate that E2 β induces de novo synthesis of ANXA1 and stimulates its secretion in the CCRF-CEM cell line, apparently through a mechanism independent of the intracellular estrogen receptor.